1998
DOI: 10.1021/ic970103r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition with Lanthanide(III) Tris(β-diketonate) Complexes:  Extraction, Transport, and Chiral Recognition of Unprotected Amino Acids

Abstract: Lipophilic lanthanide complexes of fluorinated β-diketonate ligands were demonstrated to bind unprotected phenylalanine, leucine, and other amino acids under neutral conditions. Extraction experiments supported that these lanthanide tris(β-diketonates) formed highly coordinated 1:1 complexes with amino acids, although they were electrically neutralized. NMR and CD spectroscopic studies further suggested that the lanthanide tris(βdiketonates) bound amino acids at two points. Their extraction, transport, and chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…The physical and chemical properties of the lates and when Hoard showed that edta complexes contain III resulting assembly are determined by the nature of the Ln ions with CN510 [3]. Nowadays, it is common ion-to-ligand chemical bonds and by the geometrical knowledge that large coordination numbers (7)(8)(9)(10)(11)(12) domi-III arrangement of the ligands around the metal ion. The main nate the coordination chemistry of Ln ions.…”
Section: A Slow Startmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical and chemical properties of the lates and when Hoard showed that edta complexes contain III resulting assembly are determined by the nature of the Ln ions with CN510 [3]. Nowadays, it is common ion-to-ligand chemical bonds and by the geometrical knowledge that large coordination numbers (7)(8)(9)(10)(11)(12) domi-III arrangement of the ligands around the metal ion. The main nate the coordination chemistry of Ln ions.…”
Section: A Slow Startmentioning
confidence: 99%
“…The coordiAcademic curiosity for the chemical properties of the nation number (CN), which is the number of metal-tolanthanide ions has been a constant driving force for the development of their coordination chemistry. But, in addition, practical applications soon emerged, first in the [8], while effect by Weissman [6], who demonstrated that energy chiral shift reagents probe the absolute configuration of transfer occurs from the bound ligands to the metal ion, amino acids [9,10].…”
Section: A Slow Startmentioning
confidence: 99%
“…The complexation and transport of racemic mixtures with chiral receptors has been pointed out as a smooth method for enantiomeric resolution, because it requires low concentrations of the receptor, which can be recovered at the end of the process. 17 In the literature, various types of chiral receptors bearing cyclodextrins (CDs), [18][19][20] tartaric acid derivatives, 21 crown ethers, [22][23][24] chiral complexes of transition metals, 25 carriers with porphyrin or sapphyrin rings, 26 macrocyclic pseudopeptides, 27 chiral phosphoric acids esters, 28,29 guanidine derivatives of sterols, 30,31 or cinchonidine, 32 have been reported on the chiral separation of amino acids. Although many calixarene derivatives have been synthesized as membrane carriers for anions, 33 cations, 34,35 and neutral molecules, [36][37][38] only a few investigations 39 have been reported for chiral guests.…”
Section: Introductionmentioning
confidence: 99%
“…[31] However, the enantioselective extraction of underivatized amino acids persists to be one of the great challenges within the field of ELLE. Besides the seminal work of the groups of Cram and de Mendoza, [32][33][34] proline-copper complexes [20,35] and β-diketonato-lanthanide complexes [36] have been studied with variable success. Recently we have shown that chiral palladium phosphane complexes show the highest selectivity in the enantioselective extraction of tryptophan using metal complexes thusfar reported.…”
Section: Introductionmentioning
confidence: 99%